Application of the Book Taisirul Khallaq in Building Students Morals - Musa, Sopyan Hadi (Riwayat: Educational Journal of History and Humanities, 2023)
This research illustrates the benefits of the book Taisirul Khallaq in the Islamic boarding school environment. This research uses qualitative with a pedagogical approach. The data sources in the research came from interviews, the parties interviewed were the chairman of the Foundation, supervisors, Asatidz, parents, students. The results of the research showed that 1) The book Taisirul Khallaq consists of thirty-one chapters. This book is a concise book on the science of morals. Of the thirty-one chapters, one chapter specifically discusses learning etiquette for students of science. The thing that Hafiz Hasan Al-Mas'udi prioritizes most in his book Taisirul Khallaq is instructions in soft language that is easy for students to understand. 2) Study of the book Taisirul Khallaq is held as a special activity which is held after every evening prayer congregation, precisely at 19.30-20.30. For each special activity there are two meetings, one meeting has 30 minutes for studying one book. Class 1 study of the book Taisirul Khallaq takes place once a week, which falls on Thursday evenings. Students who study the book Taisirul Khallaq at the boarding school will know more about how to be civil and civilized towards themselves, Allah, and fellow human beings.